Effects of transfer pricing rules on the income tax of companies linked to postal services - Peru - 2020 - Merino, Guillermo (2021)
This research carried out the analysis and evaluation of the incidence of the normative application of transfer prices in the Income Tax for related companies that provide postal services, a sample of 92 companies that provide postal services located in Metropolitan Lima has been carried out. , using as data collection instruments surveys directed at managers, administrators and accountants; It was found that they indicated that the accounting information reflected in the Financial Statements does not issue their internal information based on the current transfer pricing regulations, so the corresponding adjustments will have to be made through working papers for the affidavit and therefore both there will be an adjustment in the Income Tax; Therefore, the results obtained determined that if the price agreed between the related parties does not adjust to those of the free market, then it will not obtain a real tax base of the Income Tax; It has been concluded that any commercial transaction that avoids complying with the transfer price regulations (Arm’s Length principle) with related companies, and they have not made the corresponding adjustments at the end of the year by modifying the corresponding Tax, then SUNAT will make the adjustments respective and apply the corresponding sanctions; It is always recommended to be analyzing the market values under the arms legth principle and to find discrepancies with this, make the corresponding adjustments before filing the Income Tax Affidavit.